Experimental Study on Normal Frost-Heave Force Generated from Loess upon Freezing considering Multiple Factors - Zai-kun Zhao; Tie-hang Wang; Xin Jin; Yu Zhang (Advances in Materials Science and Engineering)
An experimental study on the normal frost-heave force generated by loess was conducted by subjecting loess with various water contents and densities to different temperature conditions. The experimental results show that the interaction of the three factors has a significant effect on the normal frost-heaving force. Normal frost-heave force increases exponentially with an increase in dry density and linearly with a reduction in the freezing temperature or an increase in water content; of these factors, dry density has the greatest influence on frost-heave force, followed by water content then temperature. A frost-heave force model is developed that includes overall consideration of the interactions of water content, density, and temperature based on fitting of the test results. The value calculated with the model is in good agreement with values measured in verification tests, indicating that the model has high accuracy and can provide scientific guidance for engineering design in loess areas.